2020
DOI: 10.3389/fonc.2020.00529
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic and Diagnostic Multidisciplinary Pathway for Merkel Cell Carcinoma Patients

Abstract: Merkel Cell Carcinoma (MCC) is a highly aggressive neuroendocrine neoplasm of the skin. Due to its rarity, the management of MCC is not standardized across centers. In this article, we present the experience of the Veneto region in the NorthEast of Italy, where a committee of skin cancer experts has proposed a clinical pathway for the diagnosis and treatment of MCC. Putting together the evidence available in the international literature, we outlined the best approach to the management of patients affected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…To sum up and take into consideration the absence of a coded algorithm, the therapeutic approach of each case of MCC should be discussed by a multidisciplinary group consisting of at least an oncologist, a dermatologist, a surgeon, and a radiotherapist ( 67 , 68 ).…”
Section: Treatment Of Primary Tumormentioning
confidence: 99%
“…To sum up and take into consideration the absence of a coded algorithm, the therapeutic approach of each case of MCC should be discussed by a multidisciplinary group consisting of at least an oncologist, a dermatologist, a surgeon, and a radiotherapist ( 67 , 68 ).…”
Section: Treatment Of Primary Tumormentioning
confidence: 99%
“…Merkel cell carcinoma (MCC) is a rare and highly aggressive malignancy of the skin (1)(2)(3)(4). MCC usually presents itself as a rapidly growing pink to red-violet indurated plaque or nodule on sun-damaged skin, most commonly on the head and neck and less frequently on the trunk and extremities (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…MCC is characterized by a high rate of local recurrence and nodal metastasis, a high mortality rate, and a deep psychological impact (12). The treatment regimen depends on the stage of the disease and includes surgery, radiation, chemotherapy, and/or immunotherapy (4,7,13). Surgical treatment consists of a wide excision of the primary lesion, sentinel lymph node biopsy, and/ or regional lymph node dissection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As expert opinion, an Italian group has suggested brain MRI in all cases of T2 to T4 tumors and in T1 tumors with suspected brain involvement. 3 A recent study focusing on the yield of nonbrain staging imaging in MCC revealed that 13.2% of patients with clinically node-negative disease and 10.8% of patients with clinically node-positive disease were upstaged.…”
mentioning
confidence: 99%